2001
DOI: 10.1128/jvi.75.18.8615-8623.2001
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Nucleotidyl Transferase Activity of Recombinant Flaviviridae RNA-Dependent RNA Polymerases: Implication for Viral RNA Synthesis

Abstract: Recombinant hepatitis C virus (HCV) RNA-dependent RNA polymerase (RdRp) was reported to possess terminal transferase (TNTase) activity, the ability to add nontemplated nucleotides to the 3 end of viral RNAs. However, this TNTase was later purported to be a cellular enzyme copurifying with the HCV RdRp. In this report, we present evidence that TNTase activity is an inherent function of HCV and bovine viral diarrhea virus RdRps highly purified from both prokaryotic and eukaryotic cells. A change of the highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 38 publications
8
100
2
Order By: Relevance
“…This result suggests that Cterminal region of NS5B might play a role in the initiation of RNA synthesis from 3'-end of HCV genome. To date, HCV NS5B polymerase has been shown to initiate RNA synthesis by snap-back or de novo mechanisms using a natural HCV RNA template (Behrens et al, 1996;Lohmann et al, 1997;Yamashita et al, 1998;Ishii et al, 1999;Oh et al, 2000;Sun et al, 2000;Ranjith-Kumar et al, 2001;Reigadas et al, 2001;Kashiwagi et al, 2002;Kim et al, 2002;Pellerin et al, 2002). Our results shown with several HCV RNA templates using TNTase-free NS5B are in agreement with the previous result obtained with E. coli-expressed NS5B (Oh et al, 1999), indicating that HCV NS5B proteins initiate RNA synthesis in a primer-independent manner.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This result suggests that Cterminal region of NS5B might play a role in the initiation of RNA synthesis from 3'-end of HCV genome. To date, HCV NS5B polymerase has been shown to initiate RNA synthesis by snap-back or de novo mechanisms using a natural HCV RNA template (Behrens et al, 1996;Lohmann et al, 1997;Yamashita et al, 1998;Ishii et al, 1999;Oh et al, 2000;Sun et al, 2000;Ranjith-Kumar et al, 2001;Reigadas et al, 2001;Kashiwagi et al, 2002;Kim et al, 2002;Pellerin et al, 2002). Our results shown with several HCV RNA templates using TNTase-free NS5B are in agreement with the previous result obtained with E. coli-expressed NS5B (Oh et al, 1999), indicating that HCV NS5B proteins initiate RNA synthesis in a primer-independent manner.…”
Section: Discussionsupporting
confidence: 83%
“…We have demonstrated that NS5B proteins purified from insect cells do not have intrinsic TNTase activity, in contrast to previous reports (Behrens et al, 1996;Ranjith-Kumar et al, 2001). In addition, any 3'-terminally extended products was not detected from oligouridylic acid (U)20.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Heparin RdRp Assay-The RdRp assay was performed as described previously (25), with the following modifications. Briefly, after a 15-min incubation, heparin was added to the reaction at a final concentration of 10 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The newly synthesized template-sized RNA product annealed to the unlabeled template (ϩ) RNA would be resistant to RNase A treatment. However, if the template-sized product was synthesized by a putative terminal transferase activity of WNV NS5 similar to that of the hepatitis C virus NS5B polymerase reported previously (45), then the product would be digested by RNase A. To analyze the RdRP products by RNase A digestion, the RdRP reac- FIG.…”
Section: Purification Of Full-length Wnv Ns5-we Found That E Colimentioning
confidence: 99%